Kajian Titer Antibodi Pada Yolk dari Ayam yang Diimunisasi Dengan Antigen Ekskretori/Sekretori Stadium L3 Ascaridia galli - Darmawi Darmawi; Ummu Balqis; Risa Tiuria; Muhammad Hambal; Samadi Samadi (Agricultural Faculty, 2008)
Evaluation of antibody titre in yolk from immunized chickens with excretory/secretory antigen of L3 stage of Ascaridia galliABSTRACT. The purpose of the present study was to trigger humoral immunity of chickens egg yolk exposed to excretory/secretory released in vitro by L3 stage of Ascaridia galli. Amount of 6 head chickens were divided into two groups. First group, the chickens were not immunized. Second group, the chickens were immunized with excretory/ secretory. Active immunizations with excretory/ secretory antigen were applied intra muscularly of chickens with an initial dose of 80 g. The immunizations were repeated three times with dose of each 60 g with an interval of one week. The first immunizations were excretory/secretory antigen mixed with Fruend Adjuvant Complete and subsequently mixed with Freund Adjuvant Incomplete. Antibody response in yolk was detected at weekly intervals by enzyme linked immunosorbant assay (ELISA). The result showed that antibody in yolk was begun detect with ELISA increased at two weeks after immunization, This study has shown that the excretory/secretory released in vitro by L3 stage A. galli is capable of stimulating humoral immunity by mean of producing IgY in yolk.